Head Injuries in Urban Environment Skiing and Snowboarding: A Retrospective Study on Injury Severity and Injury Mechanisms. (June 2018) - Stenroos, A.; Handolin, L.
Background and Aim: During the last decade urban skiing and snowboarding has gained a lot of popularity. In urban skiing/snowboarding riders try to balance on handrails and jump off buildings. Previous studies in skiing and snowboarding accidents have mostly been conducted at hospitals located close to alpine terrain with big ski resort areas. The aim of this study is to evaluate the types and severity of traumatic brain injuries occurring in small, suburban hills and in urban environment, and to characterize injury patterns to find out the specific mechanisms of injuries behind. Materials and Methods: This study included all patients admitted to the Helsinki University Hospital Trauma Unit from 2006 to 2015 with a head injury (ICD 10 S06-S07) from skiing or snowboarding accidents in Helsinki capital area. Head injuries that did not require a CT-scan, and injuries older than 24 hours were excluded from this study. Results: There were a total of 72 patients that met the inclusion criteria Mean length of stay in hospital was 2.95 days. According to the AIS classification, 30% had moderate, 14% had severe, and 10% had critical head injuries. Patients who got injured in terrain parks or on streets where more likely to be admitted to ICU than those injured on slopes. Based on GOS score at discharge, 78% were classified as having a good recovery from the injury, 13% had a moderate disability, 5% had a severe disability and 3% of the injuries were fatal. There were no statistically significant differences in decreased GOS between the accident sites. Conclusion: Head injuries occurring in small suburban hills and in urban environments can be serious and potentially fatal. The profile and severity of skiing injuries in urban environments and small, suburban hills is comparable to those on alpine terrain.